A cognitive analysis of influencing factors towards urbanites’ healthcare satisfaction in Bhubaneswar. - Nihar Ranjan Rout; Ram Babu Bhagat (Universiti Kebangsaan Malaysia, 2013)
Despite of the potential role of service quality analysis from the beneficiaries’perspectives in health system strengthening, its use has been limited in the developing world. More so, the analysis of socio-economic and demographic correlates of the perception differentials has been least addressed by the researchers. This study is an attempt to explore the perception of the urbanites regarding quality of health centres in Bhubaneswar, India and its socio-economic correlates.